2014
DOI: 10.12804/esj16.1.2014.03
|View full text |Cite
|
Sign up to set email alerts
|

La regulación agraria en Colombia o el eterno déjà vu hacia la concentración y el despojo: un análisis de las normas jurídicas colombianas sobre el agro (1991-2010)

Abstract: La regulación agraria en Colombia o el eterno déjà vu hacia la concentración y el despojo: un análisis de las normas jurídicas colombianas sobre el agro (1991-2010)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
2
0
5
Order By: Relevance
“…Such behaviour partly explains the significant increase of dispossession in times of armed conflict. Greater appeal to political connections and better information resources than those available to the land predators of the period from 1870 to 1940 meant that the predators of the period from 1980 to 2000 were able to scale up coercion, triggering waves of displacement (Peña‐Huertas et al, ; Peña‐Huertas, Zuleta, & Loaiza, ). As noted in the previous section, the institutions used during the armed conflict allowed the development of different means of dispossession (Table ), based on three major factors.…”
Section: The Operation Of the Mechanisms During Warmentioning
confidence: 99%
See 1 more Smart Citation
“…Such behaviour partly explains the significant increase of dispossession in times of armed conflict. Greater appeal to political connections and better information resources than those available to the land predators of the period from 1870 to 1940 meant that the predators of the period from 1980 to 2000 were able to scale up coercion, triggering waves of displacement (Peña‐Huertas et al, ; Peña‐Huertas, Zuleta, & Loaiza, ). As noted in the previous section, the institutions used during the armed conflict allowed the development of different means of dispossession (Table ), based on three major factors.…”
Section: The Operation Of the Mechanisms During Warmentioning
confidence: 99%
“…The relevant Colombian literature has shown that the assignment of property rights over land is highly exclusionary (see, e.g., LeGrand, , ; Peña‐Huertas, Parada Hernández, & Zuleta Ríos, ; Reyes Posada, ). We show through our cases that: in effect, they are exclusionary, in more senses than is identified by the literature; and that, after the onset of armed conflict, they generate incentives and mechanisms that favour massive violent accumulation of land.…”
Section: Identyfing the Problemmentioning
confidence: 99%
“…La falta de representación generó que los temas relacionados con el sector agrario, en general, y sobre los derechos campesinos, en particular, no se consideraran como un aspecto prioritario de la agenda constituyente. Por lo anterior, en la anc no existió una amplia discusión sobre las garantías que traería la nueva constitución para los campesinos (Güiza et al, 2020); de hecho, en el texto final no hay una referencia explícita a esta población (Peña Huertas et al, 2014;Peña Huertas, 2020).…”
Section: Los Objetivos Constitucionales De La Promoción Del Acceso a unclassified
“…Sobre los efectos que tuvo la Constitución de 1991 en la política agraria hay dos lecturas. La primera afirma que el texto constitucional no generó cambios significativos sobre la propiedad agraria, pues se mantuvo el régimen de propiedad individual existente (Peña et al, 2014;Sánchez, 2017). Sin embargo, esta interpretación se realizó al analizar únicamente el texto constitucional.…”
Section: Introductionunclassified
“…Sin embargo, este impacto del modelo neoliberal debe entenderse en un contexto de estructuras agrarias pre-existentes y un marco institucional que permitió su instalación (Peña Huertas et al, 2014). Dicho modelo económico no es un fenómeno natural que llegó al país, sino es el resultado de la implementación de una serie de políticas públicas que promovieron la apertura económica, las cuales pasan por un filtro o procedimiento de decisión política que depende tanto de los diseños de dichas políticas como de las constelaciones de poder en las que se crean (Gutiérrez, 3013 en Peña Huertas et al, 2014). Es decir, a través de las instituciones del Estado y sus jerarquías se consolidan las políticas aperturistas que producen esos escenarios de empobrecimiento y que son el resultado de unos arreglos políticos entre distintos sectores de la sociedad.…”
Section: La Construcción De La Pobreza En Lo Rural: Neoliberalismo Cu...unclassified